Cost-effective FRP solutions for enhancing strength and strain of sustainable concrete made with waste tyre rubber - Saingam, Panumas; Chatveera, Burachat; Hussain, Qudeer; Sua-iam, Gritsada; Chaimahawan, Preeda; Suthumma, Chisanuphong; Ahmad, Afaq (My University, 2026)
This study investigates the compressive behavior and analytical modeling of natural and rubberized concretes confined with cost-effective glass fiber-reinforced polymer (GFRP) jackets. Forty-two cylindrical specimens were tested under axial compression, including natural aggregate concrete (NAC) and rubberized concretes (RuC) prepared with 20% fine aggregate replacement using coarse (2.0 mm) and fine (0.425 mm) waste tire rubber. Both full and strip GFRP wrapping configurations with two, four, and six layers were examined. The results showed that GFRP confinement substantially enhanced both strength and ductility, transforming brittle failure into a gradual, energy-absorbing response. Full wrapping produced up to 63% and 90% strength increases for NAC and rubberized concretes, respectively, with ultimate strain gains exceeding 1300% in the fine-rubber mix. Strip wrapping achieved moderate yet significant improvements while offering material savings. Analytical models were developed for both concrete types to predict confined stress–strain behavior, achieving strong correlations (R2 = 0.84–0.99) between predicted and experimental data. The derived regression-based formulations successfully captured the influence of confinement pressure, rubber content, and wrapping configuration. These findings demonstrate that GFRP provides an economical and sustainable confinement solution for enhancing the performance of rubberized concrete in structural and retrofitting applications.
Keywords: Analytical model; Axial compression; GFRP confinement; Rubberized concrete; Sustainable materials; Waste tyre rubber